Authentication of M14 melanoma cell line proves misidentification of MDA‐MB‐435 breast cancer cell line. Issue 3 (10th October 2017) - Korch, Christopher; Hall, Erin M.; Dirks, Wilhelm G.; Ewing, Margaret; Faries, Mark; Varella‐Garcia, Marileila; Robinson, Steven; Storts, Douglas; Turner, Jacqueline A.; Wang, Ying; Burnett, Edward C.; Healy, Lyn; et al.
Abstract : A variety of analytical approaches have indicated that melanoma cell line UCLA‐SO‐M14 (M14) and breast carcinoma cell line MDA‐MB‐435 originate from a common donor. This indicates that at some point in the past, one of these cell lines became misidentified, meaning that it ceased to correspond to the reported donor and instead became falsely identified (through cross‐contamination or other means) as a cell line from a different donor. Initial studies concluded that MDA‐MB‐435 was the misidentified cell line and M14 was the authentic cell line, although contradictory evidence has been published, resulting in further confusion. To address this question, we obtained early samples of the melanoma cell line (M14), a lymphoblastoid cell line from the same donor (ML14), and donor serum preserved at the originator's institution. M14 samples were cryopreserved in December 1975, before MDA‐MB‐435 cells were established in culture. Through a series of molecular characterizations, including short tandem repeat (STR) profiling and cytogenetic analysis, we demonstrated that later samples of M14 and MDA‐MB‐435 correspond to samples of M14 frozen in 1975, to the lymphoblastoid cell line ML14, and to the melanoma donor's STR profile, sex and blood type. This work demonstrates conclusively that M14 is the authentic cell line and MDA‐MB‐435 is misidentified. With clear provenance information and authentication testing of early samples, it is possible to resolve debates regarding the origins of problematic cell lines that are widely used in cancer research. Abstract : What's new? A variety of analytical approaches have indicated that melanoma cell line M14 and breast carcinoma cell line MDA‐MB‐435 originate from a common donor, but there is ongoing debate regarding which is the misidentified cell line. Here, authentication testing of M14 from 1975 (prior to the establishment of MDA‐MB‐435), with comparison to donor serum and lymphoblastoid cell line ML14, shows that M14 is the authentic cell line and MDA‐MB‐435 is a misidentified derivative. With clear provenance information and authentication testing of early samples, debates regarding the origins of problematic cell lines that are widely used in cancer research can be resolved.